2017
DOI: 10.3390/toxins9040146
|View full text |Cite
|
Sign up to set email alerts
|

Initial Spore Density Has an Influence on Ochratoxin A Content in Aspergillus ochraceus CGMCC 3.4412 in PDB and Its Interaction with Seeds

Abstract: The morphology and secondary metabolism of Aspergillus spp. are associated with initial spore density (ISD). Fatty acids (FA) are involved in the biosynthesis of aflatoxins (AF) through Aspergillus quorum sensing (QS). Here, we studied how ochratoxin A (OTA) was regulated by spore density in Aspergillus ochraceus CGMCC 3.4412. The results contribute to understanding the role of spore density in morphogenesis, OTA biosynthesis, and host–pathogen interactions. When A. ochraceus was grown in Potato Dextrose Broth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…, the relationship between density and behavior that shown as quorum sensing has been studied for a long time. Studies of A. nidulans [ 30 ], A. parasiticus [ 31 ], A. flavus [ 32 ], and A. ochraceus [ 33 ] have found that morphological transformation and secondary metabolites are regulated in a density-dependent manner mediated by quorum sensing molecules. However, there are inconformity between existing results and the density threshold remains uncertain, which are due to differences in filamentous fungus properties and experimental conditions, but there may be more influencing factors that have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…, the relationship between density and behavior that shown as quorum sensing has been studied for a long time. Studies of A. nidulans [ 30 ], A. parasiticus [ 31 ], A. flavus [ 32 ], and A. ochraceus [ 33 ] have found that morphological transformation and secondary metabolites are regulated in a density-dependent manner mediated by quorum sensing molecules. However, there are inconformity between existing results and the density threshold remains uncertain, which are due to differences in filamentous fungus properties and experimental conditions, but there may be more influencing factors that have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…As signaling molecules, They modulate the balance between the sexual and asexual development of fungi and are involved in synthetic fungal toxins [21]. In addition, oxylipins play numerous roles in fungal physiology, inducing/repressing gene expression, conducting intra/interspecies interactions, triggering QS regulation to change population characteristics, and regulating intercellular behavior [22]. Volatile oxidized lipids are known to have antibacterial and antifungal property es and act as signaling molecules in the mutual interactions of a variety of creatures including insects, higher plants, and fungi [23].…”
Section: Introductionmentioning
confidence: 99%